Suppressive effect of pseudolaric acid B on Echinococcus multilocularis involving regulation of TGF-β1 signaling in vitro and in vivo - Gao, Haijun; Huo, Lele; Mo, Xiaojin; Jiang, Bin; Luo, Yanping; Xu, Bin; Li, Jingzhong; Ma, Xingming; Jing, Tao; Feng, Zheng; Zhang, Ting; Hu, Wei (Frontiers in Microbiology, 2022)
Echinococcus multilocularis, the causative agent of alveolar echinococcosis (AE), severely threats human health and livestock farming. The first line of chemotherapeutic drug for AE is albendazole, which limits rapid extension of E. multilocularis metacestodes, but is rarely curative for AE, with severe side effects in long-term use, thus development of new anti-echinococcal drugs is mandated. Pseudolaric acid B (PAB) has long been used to treat fungal-infected dermatosis, and exerted anti-tumor, -fertility, -angiogenesis, -tubulin and antiparasitic activity. However, the effect of PAB against Echinococcus spp. remains unclear. The present study is to understand the effect of PAB against E. multilocularis in vitro and in vivo, and identify potential anti-echinococcal mechanism, as well as its toxicity. After exposure to PAB at 20 μg/ml, significant reduction of the survival rate and substantial ultrastructural destructions in E. multilocularis protoscoleces were observed in vitro. Furthermore, the wet weight of E. multilocularis cysts in the infected mice was significantly decreased after treatment with PAB (40, 20 or 10 mg/kg) for 12 weeks. Meanwhile, significant increase of both protein and mRNA expression of transforming growth factor beta 1 (TGF-β1) was detected in the serum and liver of the infected mice, whereas PAB administration lowered its expression significantly. The toxicity tests demonstrated that PAB displayed lower cytotoxicity to human liver and kidney cells (HL-7702 and HK-2 cell) with IC50 = 25.29 and 42.94 µg/ml than albendazole with IC50 = 3.71 and 21.22 µg/ml in vitro, and caused lower hepatoxicity and nephrotoxicity in mice than ABZ. Our findings indicated that PAB possesses potent anti-echinococcal effect, with lower toxicity than albendazole, implying a potential chemotherapeutic agent for AE. Additionally, the present study demonstrated that the suppressive effect of PAB on the parasite may involve down-regulation of TGF-β1 signaling.